Recent advances in elucidating mechanisms of symbiont transmission and developmental integration in cicadas - Alex CC Wilson; Hsiao-ling Lu (Current Opinion in Insect Science, 2026)

Applying machine learning tools to advance quality control in oyster nurseries - Sarah Bodenstein; Gowri Priya Sunkara; Dow Draper; Mark C. Herpin; Austin C. Louque; Angel S. Wilson; Sanjida Nupur; Maxwell T. Shroyer; Alex Mensen Johnson; Shalini Shalini; Nadejda Drenska; Peter R. Wolenski; et al. (Aquacultural Engineering, 2026)

Influence of generations in captivity, life stage and temperature on gene expression in brain tissue of juvenile brook charr (Salvelinus fontinalis) - Ghizlane Banousse; Céline Audet; Angélina Lagneau; Alex Wilder; Chris C. Wilson; Christina A.D. Semeniuk (Aquaculture, 2026)

Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Large-scale rift-related faulting linked to a caldera-forming eruption: A case study from Taupō, New Zealand - Alex S. Gold; Madisen Snowden; James D. Muirhead; Pilar Villamor; Genevieve L. Coffey; Colin J.N. Wilson; Regine Morgenstern (Journal of Volcanology and Geothermal Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Physicochemical and structural changes of cassava starch modified by pyrodextrinization with glacial acetic acid as catalyst - Erivan de Souza Oliveira; Mighay Lovera; Alex Altair Costa Machado; Lorena Maria Freire Sampaio; Kelvi Wilson Evaristo Miranda; Angelo Roncalli Alves e Silva; Maria do Socorro Rocha Bastos; Ana Cristina de Oliveira Monteiro Moreira (Biocatalysis and Agricultural Biotechnology, 2025)

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Hemisphere- and condition-specific alpha oscillations support semantic and spatial cognition in aging - Maggie P. Rempe; Danae S. Manta; Kayle Cohen; Ryan J. Glesinger; Hannah J. Okelberry; Jason A. John; Anna T. Coutant; Lucy K. Horne; Grant M. Garrison; Kennedy A. Kress; Lucas Weyrich; Chloe C. Casagrande; et al. (GeroScience, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

One Health tropical wetlands: a transdisciplinary framework for assessing the risks of emerging zoonotic diseases in the Brazilian Pantanal - Fabio de Oliveira Roque; Heitor Miraglia Herrera; Gisele Braziliano de Andrade; Matthew Johnson; André Valle Nunes; Alessandra Gutierrez de Oliveira; Eduardo de Castro Ferreira; Geraldo Wilson Fernandes; Giulia Armani Araujo; Luiz Gustavo R. O. Santos; Rafael Morais Chiaravalloti; Reinaldo Farias Paiva de Lucena; et al. (Wetlands Ecology and Management, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Broad immunogenicity to prior SARS-CoV-2 strains and JN.1 variant elicited by XBB.1.5 vaccination in nursing home residents - Yasin Abul; Clare Nugent; Igor Vishnepolskiy; Tiffany Wallace; Evan Dickerson; Laurel Holland; Iva Esparza; Mandi Winkis; Kazi Tanvee Wali; Philip A. Chan; Rosa R. Baier; Amy Recker; et al. (GeroScience, 2024)

Estimating age-at-maturity for individual Atlantic bluefin tuna (Thunnus thynnus) from back-calculated growth trajectories - Nathan D. Stewart; Kyle L. Wilson; Alex Hanke (Fisheries Research, 2024)

Efficient oxidation attenuates porewater‐derived methane fluxes in mangrove waters - Yvonne Y. Y. Yau; Alex Cabral; Gloria Reithmaier; Luiz C. Cotovicz; João Barreira; Gwenaël Abril; Cedric Morana; Alberto V. Borges; Wilson Machado; José M. Godoy; Stefano Bonaglia; Isaac R. Santos (Limnology and Oceanography, 2024)
Mangroves store significant amounts of carbon in both sediment and water. Methane (CH 4 ) is often produced in anoxic, organic‐rich sediments during carbon degradation and released to overlying waters via porewater exchange. Yet, a portion of CH 4 can be oxidized to CO 2 before emission. Here, we investigate whether CH 4 oxidation impacts its emissions using high‐temporal resolution CH 4 concentration and stable isotope (δ 13 C‐CH 4 ) observations collected over 14 tidal cycles in 2 Brazilian mangrove creeks with no river inputs. We found higher CH 4 concentrations (~ 150 nM) more depleted in 13 C (−75‰) during low tide than high tide at both creeks. Similar δ 13 C‐CH 4 values between low tide surface waters and porewaters further suggest tidally driven porewater exchange as the main source of CH 4 . More 13 C‐enriched CH 4 in surface waters and surface sediments than deep sediments indicate partial CH 4 oxidation prior to exchange with the atmosphere. A stable isotope mass balance revealed that 17–58% of CH 4 was oxidized at rates of 3–25 μ mol m −2 d −1 in the water column of tidal creeks. A larger portion of deep porewater CH 4 (45–61%) was oxidized in sediments prior to porewater exchange with surface creek waters. The two mangrove creeks had average water–air CH 4 fluxes of 51–109 μ mol m −2 d −1 over spring‐neap tidal cycles. These aquatic CH 4 emissions offset only 4 oxidation in both surface water and sediment attenuated CH 4 emissions to the atmosphere.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Effects of generations in captivity and elevated rearing temperature on Ontario hatchery brook trout (Salvelinus fontinalis) fry quality and survival - Alex Wilder; Chris C. Wilson; Theresa R. Warriner; Christina A. D. Semeniuk (Environmental Biology of Fishes, 2024)

Isolation of intake mediated effects demonstrate that the phenomic benefits of dietary omega-3 are nominal to Atlantic salmon when reared in a challenging (hypoxic) environment - Brett D. Glencross; Alex Berry; Ben Clokie; Ernst Hevroy; David Huyben; Laura Martinez-Rubio; Chessor A. Mathew; Pedro Munoz; Simon MacKenzie; Rod W. Wilson (Aquaculture, 2024)

Modulation of movement-related oscillatory signatures by cognitive interference in healthy aging - Yasra Arif; Jake J. Son; Hannah J. Okelberry; Hallie J. Johnson; Madelyn P. Willett; Alex I. Wiesman; Tony W. Wilson (GeroScience, 2024)

Assessing hydrological controls on the lithium isotope weathering tracer - Philip A.E. Pogge von Strandmann; Lara R. Cosford; Chun-Yao Liu; Xianyi Liu; Alexander J. Krause; David J. Wilson; Xiaoqing He; Alex J. McCoy-West; Sigurður R. Gislason; Kevin W. Burton (Chemical Geology, 2023)

Individual variation and repeatability of Atlantic tarpon Megalops atlanticus migrations in the southern US: implications for conservation and management - Lucas P. Griffin; Jacob W. Brownscombe; Aaron J. Adams; JoEllen K. Wilson; Grace A. Casselberry; Peter E. Holder; Alex Filous; Susan K. Lowerre-Barbieri; Steven J. Cooke; Andy J. Danylchuk (Marine Biology, 2023)

Australian soil microbiome: A first sightseeing regional prediction driven by cycles of soil temperature and pedogenic variations - Vanessa Pino; Mario Fajardo; Alex McBratney; Budiman Minasny; Neil Wilson; Chris Baldock (Molecular Ecology, 2023)
Declines in soil multifunctionality (e.gsoil capacity to provide food and energy) are closely related to changes in the soil microbiome (e.g., diversity) Determining ecological drivers promoting such microbiome changes is critical knowledge for protecting soil functions. However, soil‐microbe interactions are highly variable within environmental gradients and may not be consistent across studies. Here we propose that analysis of community dissimilarity (β‐diversity) is a valuable tool for overviewing soil microbiome spatiotemporal changes. Indeed, β‐diversity studies at larger scales (modelling and mapping) simplify complex multivariate interactions and refine our understanding of ecological drivers by also giving the possibility of expanding the environmental scenarios. This study represents the first spatial investigation of β‐diversity in the soil microbiome of New South Wales (800,642 km 2 ), Australia. We used metabarcoding soil data (16S rRNA and ITS genes) as exact sequence variants (ASVs) and UMAP (Uniform Manifold Approximation and Projection) as the distance metric. β‐Diversity maps (1000‐m resolution)—concordance correlations of 0.91–0.96 and 0.91–0.95 for bacteria and fungi, respectively—showed soil biome dissimilarities driven primarily by soil chemistry—pH and effective cation exchange capacity (ECEC)—and cycles of soil temperature—land surface temperature (LST‐phase and LST‐amplitude). Regionally, the spatial patterns of microbes parallel the distribution of soil classes (e.g., Vertosols) beyond spatial distances and rainfall, for example. Soil classes can be valuable discriminants for monitoring approaches, for example pedogenons and pedophenons. Ultimately, cultivated soils exhibited lower richness due to declines in rare microbes which might compromise soil functions over time.

Synergistic benefits of recovered carbon black demineralisation for tyre recycling - Alex J Bowles; Amy L Wilson; Geoffrey D Fowler (Resources, Conservation and Recycling, 2023)

Recent parallel speciation in Antirrhinum involved complex haplotypes and multiple adaptive characters - Matthew Barnbrook; Mario Durán‐Castillo; Jo Critchley; Yvette Wilson; Alex Twyford; Andrew Hudson (Molecular Ecology, 2023)
A role of ecological adaptation in speciation can be obscured by stochastic processes and differences that species accumulate after genetic isolation. One way to identify adaptive characters and their underlying genes is to study cases of speciation involving parallel adaptations. Recently resolved phylogenies reveal that alpine morphology has evolved in parallel in the genus Antirrhinum (snapdragons): first in an early split of an alpine from a lowland lineage and, more recently, from within the lowland lineage to produce closely related sympatric species with contrasting alpine and lowland forms. Here, we find that two of these later diverged sympatric species are differentiated by only around 2% of nuclear loci. Though showing evidence of recent gene flow, the species remain distinct for a suite of morphological characters typical of earlier‐diverged alpine or lowland lineages and their morphologies correlate with features of the local landscape, as expected of ecological adaptations. Morphological differences between the two species involve multiple, unlinked genes so that parental character combinations are readily broken up by recombination in hybrids. We detect little evidence for post‐pollination barriers to gene flow or recombination, suggesting that genetic isolation related to ecological adaptation is important in maintaining character combinations and might have contributed to parallel speciation. We also find evidence that genes involved in the earlier alpine‐lowland split were reused in parallel evolution of alpine species, consistent with introgressive hybridisation, and speculate that many non‐ecological barriers to gene flow might have been purged during the process.

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Barriers to chimpanzee gene flow at the south‐east edge of their distribution - Noémie Bonnin; Alex K. Piel; Richard P. Brown; Yingying Li; Andrew Jesse Connell; Alexa N. Avitto; Jean P. Boubli; Adrienne Chitayat; Jasmin Giles; Madhurima S. Gundlapally; Iddi Lipende; Elizabeth V. Lonsdorf; et al. (Molecular Ecology, 2023)
Populations on the edge of a species' distribution may represent an important source of adaptive diversity, yet these populations tend to be more fragmented and are more likely to be geographically isolated. Lack of genetic exchanges between such populations, due to barriers to animal movement, can not only compromise adaptive potential but also lead to the fixation of deleterious alleles. The south‐eastern edge of chimpanzee distribution is particularly fragmented, and conflicting hypotheses have been proposed about population connectivity and viability. To address this uncertainty, we generated both mitochondrial and MiSeq‐based microsatellite genotypes for 290 individuals ranging across western Tanzania. While shared mitochondrial haplotypes confirmed historical gene flow, our microsatellite analyses revealed two distinct clusters, suggesting two populations currently isolated from one another. However, we found evidence of high levels of gene flow maintained within each of these clusters, one of which covers an 18,000 km 2 ecosystem. Landscape genetic analyses confirmed the presence of barriers to gene flow with rivers and bare habitats highly restricting chimpanzee movement. Our study demonstrates how advances in sequencing technologies, combined with the development of landscape genetics approaches, can resolve ambiguities in the genetic history of critical populations and better inform conservation efforts of endangered species.

Climate-driven shifts in pelagic fish distributions in a rapidly changing Pacific Arctic - Robert M. Levine; Alex De Robertis; Daniel Grünbaum; Sharon Wildes; Edward V. Farley; Phyllis J. Stabeno; Christopher D. Wilson (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Distinctive role of soil type and land use in driving bacterial communities and carbon cycling functions down soil profiles - Peipei Xue; Budiman Minasny; Alex McBratney; Neil L. Wilson; Yijia Tang; Yu Luo (CATENA, 2023)

Modifying a pelagic trawl to better retain small Arctic fishes - Alex De Robertis; Robert Levine; Kresimir Williams; Christopher Wilson (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Correction to: Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

An Analysis of the Technical and Economic Influences of Particle Size Control of an Active Pharmaceutical Ingredient - David Wilson; Alex Crampton; Rachel Sullivan; Alexander Liljeblad (Journal of Pharmaceutical Innovation, 2022)

Soil bacterial depth distribution controlled by soil orders and soil forms - Peipei Xue; Alex B. McBratney; Budiman Minasny; Tony O’Donnell; Vanessa Pino; Mario Fajardo; Wartini Ng; Neil Wilson; Rosalind Deaker (Soil Ecology Letters, 2022)

Microbiome and oral squamous cell carcinoma: a possible interplay on iron metabolism and its impact on tumor microenvironment - Rodrigo Alex Arthur; Rafael dos Santos Bezerra; João Paulo Bianchi Ximenez; Bruna Laís Merlin; Raphael de Andrade Morraye; João Valentini Neto; Natália Melo Nasser Fava; David Livingstone Alves Figueiredo; Carlos Alberto Oliveira de Biagi; Maria Jara Montibeller; Jhefferson Barbosa Guimarães; Ellen Gomes Alves; et al. (Brazilian Journal of Microbiology, 2021)

Altered fronto-occipital connectivity during visual selective attention in regular cannabis users - Abril Rangel-Pacheco; Brandon J. Lew; Mikki D. Schantell; Michaela R. Frenzel; Jacob A. Eastman; Alex I. Wiesman; Tony W. Wilson (Psychopharmacology, 2021)

Navigating the link between processing speed and network communication in the human brain - Phoebe Imms; Juan F. Domínguez D; Alex Burmester; Caio Seguin; Adam Clemente; Thijs Dhollander; Peter H. Wilson; Govinda Poudel; Karen Caeyenberghs (Brain Structure and Function, 2021)

Effects of high-carbohydrate versus mixed-macronutrient meals on female soccer physiology and performance - Jaison L. Wynne; Alex M. Ehlert; Patrick B. Wilson (European Journal of Applied Physiology, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Compositions and mobility of major, δD, δ18O, trace, and REEs patterns in water sources at Benue River Basin—Cameroon: implications for recharge mechanisms, geo-environmental controls, and public health - Wilson Y. Fantong; Therese L. L. Jokam Nenkam; Pierre Nbendah; Sharon B. Kimbi; Ernest Chi Fru; Brice T. Kamtchueng; Alain F. Takoundjou; Alex R. Tejiobou; Gabriel Ngueutchoua; Robert Kringel (Environmental Geochemistry and Health, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Quantitative trait loci associated with trichomes in the Solanum galapagense accession LA1401 - Marcela Carvalho Andrade; Alex Antônio da Silva; Regis de Castro Carvalho; Juliana de Andrade Santiago; Alisson Marcel Souza de Oliveira; David Merrill Francis; Wilson Roberto Maluf (Genetic Resources and Crop Evolution, 2018)

When is overkill optimal? Tritrophic interactions reveal new insights into venom evolution - Alex N. Gangur; Jamie E. Seymour; Michael J. Liddell; David Wilson; Michael J Smout; Tobin D. Northfield (Theoretical Ecology, 2018)

Recognizing conserved non-canonical localization patterns of toll-like receptors in tissues and across species - Glenn Hamonic; J. Alex Pasternak; Heather L. Wilson (Cell and Tissue Research, 2018)

microRNA regulation in an ancient obligate endosymbiosis - Honglin Feng; Lingyu Wang; Stefan Wuchty; Alex C. C. Wilson (Molecular Ecology, 2018)
Although many insects are associated with obligate bacterial endosymbionts, the mechanisms by which these host/endosymbiont associations are regulated remain mysterious. While micro RNA s (mi RNA s) have been recently identified as regulators of host/microbe interactions, including host/pathogen and host/facultative endosymbiont interactions, the role mi RNA s may play in mediating host/obligate endosymbiont interactions is virtually unknown. Here, we identified conserved mi RNA s that potentially mediate symbiotic interactions between aphids and their obligate endosymbiont, Buchnera aphidicola . Using small RNA sequence data from Myzus persicae and Acyrthosiphon pisum , we annotated 93 M. persicae and 89 A. pisum mi RNA s, among which 69 were shared. We found 14 mi RNA s that were either highly expressed in aphid bacteriome, the Buchnera ‐housing tissue, or differentially expressed in bacteriome vs. gut, a non‐ Buchnera ‐housing tissue. Strikingly, 10 of these 14 mi RNA s have been implicated previously in other host/microbe interaction studies. Investigating the interaction networks of these mi RNA s using a custom computational pipeline, we identified 103 mi RNA :: mRNA interactions shared between M. persicae and A. pisum . Functional annotation of the shared mRNA targets revealed only two over‐represented cluster of orthologous group categories: amino acid transport and metabolism, and signal transduction mechanisms. Our work supports a role for mi RNA s in mediating host/symbiont interactions between aphids and their obligate endosymbiont Buchnera . In addition, our results highlight the probable importance of signal transduction mechanisms to host/endosymbiont coevolution.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

Inheritance of type IV glandular trichome density and its association with whitefly resistance from Solanum galapagense accession LA1401 - Marcela Carvalho Andrade; Alex Antônio da Silva; Irã Pinheiro Neiva; Izabela Regina C. Oliveira; Evaristo Mauro De Castro; David Merrill Francis; Wilson Roberto Maluf (Euphytica, 2017)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

The evolution of novel host use is unlikely to be constrained by trade‐offs or a lack of genetic variation - Zachariah Gompert; Joshua P. Jahner; Cynthia F. Scholl; Joseph S. Wilson; Lauren K. Lucas; Victor Soria‐Carrasco; James A. Fordyce; Chris C. Nice; C. Alex Buerkle; Matthew L. Forister (Molecular Ecology, 2015)
The genetic and ecological factors that shape the evolution of animal diets remain poorly understood. For herbivorous insects, the expectation has been that trade‐offs exist, such that adaptation to one host plant reduces performance on other potential hosts. We investigated the genetic architecture of alternative host use by rearing individual Lycaeides melissa butterflies from two wild populations in a crossed design on two hosts (one native and one introduced) and analysing the genetic basis of differences in performance using genomic approaches. Survival during the experiment was highest when butterfly larvae were reared on their natal host plant, consistent with local adaptation. However, cross‐host correlations in performance among families (within populations) were not different from zero. We found that L. melissa populations possess genetic variation for larval performance and variation in performance had a polygenic basis. We documented very few genetic variants with trade‐offs that would inherently constrain diet breadth by preventing the optimization of performance across hosts. Instead, most genetic variants that affected performance on one host had little to no effect on the other host. In total, these results suggest that genetic trade‐offs are not the primary cause of dietary specialization in L. melissa butterflies.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans - Jaclyn Ellis; Ethan M. Lange; Jin Li; Josee Dupuis; Jens Baumert; Jeremy D. Walston; Brendan J. Keating; Peter Durda; Ervin R. Fox; Cameron D. Palmer; Yan A. Meng; Taylor Young; et al. (Human Genetics, 2014)

Dynamic recruitment of amino acid transporters to the insect/symbiont interface - Rebecca P. Duncan; Filip Husnik; James T. Van Leuven; Donald G. Gilbert; Liliana M. Dávalos; John P. McCutcheon; Alex C. C. Wilson (Molecular Ecology, 2014)
Symbiosis is well known to influence bacterial symbiont genome evolution and has recently been shown to shape eukaryotic host genomes. Intriguing patterns of host genome evolution, including remarkable numbers of gene duplications, have been observed in the pea aphid, a sap‐feeding insect that relies on a bacterial endosymbiont for amino acid provisioning. Previously, we proposed that gene duplication has been important for the evolution of symbiosis based on aphid‐specific gene duplication in amino acid transporters ( AAT s), with some paralogs highly expressed in the cells housing symbionts (bacteriocytes). Here, we use a comparative approach to test the role of gene duplication in enabling recruitment of AAT s to bacteriocytes. Using genomic and transcriptomic data, we annotate AAT s from sap‐feeding and non sap‐feeding insects and find that, like aphids, AAT gene families have undergone independent large‐scale gene duplications in three of four additional sap‐feeding insects. RNA ‐seq differential expression data indicate that, like aphids, the sap‐feeding citrus mealybug possesses several lineage‐specific bacteriocyte‐enriched paralogs. Further, differential expression data combined with quantitative PCR support independent evolution of bacteriocyte enrichment in sap‐feeding insect AAT s. Although these data indicate that gene duplication is not necessary to initiate host/symbiont amino acid exchange, they support a role for gene duplication in enabling AAT s to mediate novel host/symbiont interactions broadly in the sap‐feeding suborder Sternorrhyncha. In combination with recent studies on other symbiotic systems, gene duplication is emerging as a general pattern in host genome evolution.

Specificity, rank preference, and the colonization of a non-native host plant by the Melissa blue butterfly - M. L. Forister; C. F. Scholl; J. P. Jahner; J. S. Wilson; J. A. Fordyce; Z. Gompert; D. R. Narala; C. Alex Buerkle; C. C. Nice (Oecologia, 2013)

Of mast and mean: differential‐temperature cue makes mast seeding insensitive to climate change - Dave Kelly; Andre Geldenhuis; Alex James; E. Penelope Holland; Michael J. Plank; Robert E. Brockie; Philip E. Cowan; Grant A. Harper; William G. Lee; Matt J. Maitland; Alan F. Mark; James A. Mills; et al. (Ecology Letters, 2013)
Mast‐seeding plants often produce high seed crops the year after a warm spring or summer, but the warm‐temperature model has inconsistent predictive ability. Here, we show for 26 long‐term data sets from five plant families that the temperature difference between the two previous summers (ΔT) better predicts seed crops. This discovery explains how masting species tailor their flowering patterns to sites across altitudinal temperature gradients; predicts that masting will be unaffected by increasing mean temperatures under climate change; improves prediction of impacts on seed consumers; demonstrates that strongly masting species are hypersensitive to climate; explains the rarity of consecutive high‐seed years without invoking resource constraints; and generates hypotheses about physiological mechanisms in plants and insect seed predators. For plants, ΔT has many attributes of an ideal cue. This temperature‐difference model clarifies our understanding of mast seeding under environmental change, and could also be applied to other cues, such as rainfall.

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Simian immunodeficiency virus-specific CD4+ T cells from successful vaccinees target the SIV Gag capsid - Juan P. Giraldo-Vela; Alex T. Bean; Richard Rudersdorf; Lyle T. Wallace; John T. Loffredo; Priscilla Erickson; Nancy A. Wilson; David I. Watkins (Immunogenetics, 2010)

The importance of reproductive strategies in population genetic approaches to conservation: an example from the marine angiosperm genus Zostera - Jim Provan; Siân Wilson; Alex A. Portig; Christine A. Maggs (Conservation Genetics, 2008)

Marine systems: moving into the genomics era - Karen Wilson; Michael Thorndyke; Frank Nilsen; Alex Rogers; Pedro Martinez (Marine Ecology, 2005)
The study of biological systems has been revolutionized by the use of genomic technologies. Most of the knowledge gathered over the last few years refers to terrestrial models. The study of marine systems using genomic technologies has, apart from a focus on microbial systems, been generally neglected although there are signs that this situation may be changing. This review analyses recent progress made in the field of marine genomics and identifies the broad areas in which this new technology is having the greatest impacts. These studies include comparative, functional and environmental genomics of metazoan animals. In many cases, as well as benefiting marine science, studies on marine taxa are having wide‐ranging impacts on our global understanding of genomes and genomics.

Small is Beautiful U.S. House Size, Resource Use, and the Environment - Alex Wilson; Jessica Boehland (Journal of Industrial Ecology, 2005)
Summary As house size increases, resource use in buildings goes up, more land is occupied, increased impermeable surface results in more storm‐water runoff, construction costs rise, and energy consumption increases. In new, single‐family houses constructed in the United States, living area per family member has increased by a factor of 3 since the 1950s. In comparing the energy performance of compact (small) and large single‐family houses, we find that a small house built to only moderate energy‐performance standards uses substantially less energy for heating and cooling than a large house built to very high energy‐performance standards. This article examines some of the trends in single‐family house building in the United States and provides recommendations for downsizing houses to improve quality and resource efficiency.

Ontogenetic shifts in fusion?rejection thresholds in a colonial marine hydrozoan, Hydractinia symbiolongicarpus - Alex C. C. Wilson; Richard K. Grosberg (Behavioral Ecology and Sociobiology, 2004)

Selenocysteine lyase activity in a cysteine-requiring mutant ofEscherichia coli K-12 - Judy A. Karle; Karl A. Wilson; Alex Shrift (Biological Trace Element Research, 1986)